Kebolehan Suami Memukul Istri Karena Nusyuz (Studi Terhadap Pemahaman Masyarakat Tentang Surat al-Nisa’ ayat 34 di Kecamatan Gading Cempaka Kota Bengkulu) - Suryani Suryani; Zurifah Nurdin (IAIN Bengkulu, 2020)
In al-Qur'an, it is stated that there is the ability of a husband to beat his wife when he is defieding, that skill is sometimes used as a legitimacy for domestic violence, without understanding that ability has the terms and conditions set by the Qur'an and hadith. There are even people who do not know that there is a verse that allows the beating, what if the wife of Husband with the existing provisions, they only determine that the husband is the leader and head of the family that must be obeyed, therefore the husband does not have the right to beat the wife. This study tries to uncover the community's understanding of the verse that melts the husband who hits an incoherent wife with the household problems that exist in the community by using a sociological and psychological approach and a text approach with the study of family fiqh. The results showed there was no relevance between violence or beating of the wife with the understanding of ayat Q.S: al-Nisa ': 34:, because the violence occurred by itself because of ego factors, lack of knowledge and understanding of religious teachings, lack of education and culture or culture or tradition